Sensing properties of chitosan and chitosan-roselle film sensors on toluene concentrations detection - Halimatussa'adiah Adnan (School of Materials Engineering, University Malaysia Perlis, 2013)
This study aims to observe the sensing properties of chitosan sensor (CS) and chitosan-roselle sensors (CRSs) on toluene at various concentrations. CRSs were deposited using various chitosan: roselle ratio of 99:1 to 89:11 to find the optimum ratio which exhibit the best electrical properties. Toluene is a suitable chemical marker for lung cancer diagnosis where 30 ppb toluene in exhaled breath is regarded to be a distinctive early symptom of lung cancer.